Persepsi Manfaat dan Kemudahan dalam Penggunaan E-wallet DANA: Studi Adopsi Teknologi Finansial Digital pada Mahasiswa Universitas Dinamika Bangsa - Molwen, Elsa; Caroline, Caroline; Tamia, Brenda Aouren; Yulina, Putri Dea; Lie, Jason; Yossinomita, Yossinomita (LPPM STIKOM Dinamika Bangsa, 2025)
In the digital era, financial technology has become an essential part of everyday life, particularly for students who are highly adaptive to innovations such as electronic wallets. This study aims to analyze the effect of perceived usefulness (PU) on the use of the DANA e-wallet among students of Universitas Dinamika Bangsa (UNAMA), with perceived ease of use (PEOU) as a mediating variable. The research employed a quantitative approach by distributing questionnaires and analyzing the data using SmartPLS. The findings reveal that PU significantly influences both PEOU and actual use (AU). However, PEOU does not have a significant effect on AU, and PU through PEOU also does not significantly influence AU. These results indicate that although perceived usefulness is the primary factor driving e-wallet adoption, perceived ease of use does not act as a strong mediating variable. This study recommends that e-wallet providers focus on enhancing useful features and offering user education to improve the experience and adoption of financial technology among students.